Biswas-Milovic Model with Quadratic-Cubic Law and Its Optical Solitons - Korpinar, Zeliha; İnç, Mustafa (Amer Scientific Publishers, 2018)
In this article, as a generalized model by using the extended generalizing Riccati mapping method, optical solitons are obtained for the Biswas-Milovic equation. This method reveals several optical solitons including traveling wave solutions. The found solutions are identified with different forms including the hyperbolic functions, the rational functions and the trigonometric functions. Reliability of our solution is given graphical consequens.
Keywords: Optical Solitons; Traveling Wave Solutions; Biswas-Milovic Equation; Extended Riccati Mapping Method; Quadratic-Cubic Law